The dynamics of mixed group work in British higher education - Signorini, P. (2011)
This study examines culturally diverse groups, teams formed by home students and international students completing group tasks in Higher Education, referred to as mixed groups. This investigation differs from previous studies, and hence contributes to the existing knowledge in the field, in that it combines observational data and the use of Activity Theory as an analytical framework for furthering our understanding of group dynamics and task completion of mixed groups. This research addresses four research questions: what are students' experiences of mixed group work? What are the group dynamics in mixed groups? How do students mediate during mixed group work? What factors influences task completion in mixed groups? The study is based upon two group case studies, consisting of a non-assessed written group task and an assessed group presentation. Both case studies involved postgraduate students within the same British university. Qualitative analysis of observation and interview data revealed that students had different experiences of their group work, even among co-workers. Few group interactions were related to discussing cultural issues, highlighting the limitations that mixed group work may have in fostering internationalisation. The group dynamics described include students' interactions around: achieving a common understanding of the task, sanctioning members and conflicts regarding tool use. Both home and international students mediated in task completion in the following ways: a) acting as sources of knowledge, b) helping other members to understand the activity, and c) helping others use and learn about artefacts required in the completion of the group task and other university activities. Factors that appeared to influence mixed group work (MGW) included international students' self confidence in their spoken English, familiarity, students' positioning of self and other colleagues, expected roles, task and assessment design, and students' engagement in clarification during task completion. Some of these findings are consistent with existing literature. Finally, Activity Theory (AT) as an analytical framework was found to be useful.